Barney's Christmas Wishes - White, Stephen (Puffin Book Ltd, 1997)
In the second Christmas book starring Barney and his pals, the gentle purple dinosaur, BJ, and Baby Bop make a visit to the North Pole to see Santa Claus just before the big day.
Keywords: Juvenile Nonfiction Book